Problems and Challenges to English Language in Madaris of Pakistan - Karim Dad; Hafiz Muhammad Ibrahim (Journal of Islamic and Religious Studies, 2018)
Language is a communication tool to impart education at every level that is why different languages are taught for this purpose. In Madaris of Pakistan, Arabic is commonly taught as it is the language of basic Islamic sources i.e. The Holy Quran and Hadith. This paper will basically try to understand the learning of English as a language is not given importance, although it is very essential nowadays but besides this, it faces many problems and challenges in religious Madaris of Pakistan. Many factors are involved in this situation. In modern world, English language specially can be very helpful to the purposes of these Madaris. Learning of English language will help to impart, propagate and defend the message of Islam on a larger and wider scale. One can use it for da’wah and calling others to Allah. But some elements of Madaris are not well informed about to this fact that they have not such a larger vision to understand and absorb the facts. On the other side, supporters of teaching English language in Madaris are unluckily blind to the positive, historic, reformative role of Madaris. This situation is creating misunderstandings and these bodies are seen opponents while they must be supporting to each other. This article reviews the challenges and the problem and challenges to English language in Madaris as well as how to bridge the chasm created between the two schools of thought.